MODEL PENINGKATAN KINERJA KARYAWAN MELALUI KUALITAS KEHIDUPAN KERJA - Heri Setyo Utomo; Marno Nugroho (Department of Management, Faculty of Economics, Universitas Islam Sutan Agung, Semarang, 2014)
Competitive rivalry in business world demand the company for thinking how the way company take adapt with kaleidoscopic environment. The company must think that employees must feel enjoy with the job and their work environment so they get the best performance. Because of human resources is the most valuable asset so the company must be responsible to keep quality of work life. It’s not only quality of work life but also commitment of organization and job satisfaction need to be noticed for raising employees’ performance. In unit of production of Suara Merdeka Semarang, quality of work life, commitment of organization and job satisfaction need to be noticed. The objectives of the research is to describe and analyze the influence ofquality of work life towards job performance, to describe and analyze the influence of quality of work life towards employees commitment of organization, to describe and analyze the influence of commitment of organization towards employees’ performance, to describe and analyze the influence of job satisfaction towards employees’ performance. This research is explanatory research. The population of this research is the entire of unit of production of Suara Merdeka employees, the number of total sampling is 69 people using definite criteria such as the minimum work period is 5 years and the age of the employees is 25 years old. The kind of data is primary with using data collection method is questionnaires. Analysis instrument that areused in this research is Partial Least Square (PLS). The result of this research is quality of the work life has positive effect and significance towards employees’ performance. It means that if quality of work life is increased, employees’ performance is increased too. Quality of work life has positive effect and significance towards commitment of organization. It means that if quality of work life is increased, commitment of organization is increased too. Quality of work life has positive effect and significance towards job satisfaction. It means that if quality of work life isincreased, job satisfaction is increased too. Commitment of organization has positive effect and significance towards employees’ performance. It means that if commitment of organization is increased, employees’ performance is increased too. Job satisfaction has positive effect and significance towards employees’ performance. It means that if job satisfaction is increased, employees’ performance is increased too.Keywords : Quality Of Work Life, Commitment Of Organization, Job Satisfaction, Employees’ Performance